Validation of a management competency assessment tool for health service managers. Issue 1 (19th March 2018) - Howard, Peter F.; Liang, Zhanming; Leggat, Sandra; Karimi, Leila
Abstract : Purpose: The purpose of this paper is to report on the validation of a management competency assessment tool for health services managers (HSM), which resulted from the development and validation of the framework, addressed by a previous paper. Design/methodology/approach: The management competency assessment tool (MCAP Tool) was validated using assessment data from a sample of 117 senior and middle managers working in two public hospitals and five community services in Victoria, Australia. The assessments were conducted between January 2013 and September 2014. Findings: Both validity and reliability of the MCAP Tool were demonstrated. Practical implications: The MCAP Tool has the potential to assist in the measurement of the competencies of HSM. Further research is required to determine if the framework and tool are applicable to HSM in other settings. Originality/value: This is the first published study outlining the validity and reliability of an assessment tool to measure the management competencies of Australian health service managers.